Reflections on the Morality of Some Prophetic Acts in Zimbabwe’s Pentecostal Movements - Chimuka, Tarisayi A. (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
This essay investigates the re-emergence and proliferation of prophetic or charismatic movements in contemporary Zimbabwe. One wonders what has kindled this revival: Is it a fulfillment of the end of time as prophesied in Scripture? Has the Christian church in Africa got a new commission? Is it a sign of apostasy of the last days? Is it just an indication of self-fulfilling agendas of those involved? The paper discusses arguments on both sides of the divide. It hopes to draw useful inferences from the manifesting phenomena which will deepen our understanding on the matter.
free